Ultraviolet irradiation-responsive dynamic ultralong organic phosphorescence in polymeric systems - Yongfeng Zhang (Nature Portfolio, 2021)
Efficient stimulus-responsive phosphorescence organic materials are attractive, but are extremely rare because of unclear design principles and intrinsically spin-forbidden intersystem crossing. Here, the authors present a facile strategy to achieve ultraviolet irradiation-responsive ultralong room-temperature phosphorescence in several simple amorphous polymer materials.